Phenotypic and Genetic Diversity Evaluation of Sengon (Falcataria moluccana (Miq.) Barneby & JW Grimes) from Solomon Provenance on Progeny Trial in Cirangsad Experimental Forest, West Java - Fifi Gus Dwiyanti; Iskandar Zulkarnaen Siregar; Ulfah Juniarti Siregar (Institut Pertanian Bogor (IPB University), 2021)
Initial evaluation of phenotypic variability and genetic diversity was conducted on the progeny test of 2 years-old sengon from Solomon provenance, which derived from nine families of mother tree and were then planted in 4 blocks in the Cirangsad Experimental Forest. Phenotypic assessment on eight traits was conducted on 36 trees using a scoring system, while genetic diversity of 15 selected individuals which represented high and low-score phenotypic traits was analyzed using 5 selected RAPD primers. The result on phenotypic assessment showed that family 3 (57.25 points) has the highest average score of phenotypic quality and family 4 has the lowest average score (7.50 points). Furthermore, genetic analysis showed that the low-scoring sengon population had a greater mean genetic diversity (He = 0.2535) than the high-score population (He = 0.2345). The analysis of molecular variance (AMOVA) revealed a significant genetic differences (p-value < 0.001) among high and low-score populations and the dendrogram of genetic distance revealed clustering of individuals having similar superior phenotypic against those having non-superior, indicating the selection based on phenotypes in this study had succeeded in pooling the good quantitative alleles in the selected population. This evaluation results can be used as a reference in determining the best families to produce superior sengon (from Solomon provenance) offspring in the future that have desired adaptability, productivity, and diversity.